Determination the values of Ultra Violet Radiation intensity at Ulaanbaatar - G, Batsukh; S, Lantuu; J, Gombojav; D, Khaltar (Scientific transaction of the National University of Mongolia. Physics, 2022)
The methods and primary results of the Ultra Violet Radiation investigation from measurement data of integral solar radiation at Ulaanbaatar. Solar radiation measurements were performed with the help of thermoelectric actinometer AT-50 and pyranometer M-80. For the calculation of Ultra violet radiation has been used the simpled model of the Earth atmosphere developed by V.A. Belinsky. Using thse data we calculated the values of direct, diffised and global Ultra Violet Radiation.